The role of financial ratios and corporate governance mechanisms in predicting fraudulent financial reporting - Busro, Haziyah Nazifah; Mohammed, Nor Farizal; Mohamed, Norazida (UiTM Cawangan Johor, 2025)
This study examines the relationship between financial ratios, corporate governance and fraudulent financial reporting (FFR) and whether corporate governance moderates the relationship between financial ratios and FFR of Malaysian public listed companies (PLCs). Twenty FFR companies are selected from the Securities Commission Enforcement Release (SCER) listed by Malaysia's Securities Commission for furnishing false statements from 2000 to 2021, and twenty non-FFR companies as a control sample based on similar industries, periods, and sizes. The panel logistic regression model was adopted to analyse the research hypotheses. The total number of observations over four years is 160 companies. FFR companies are found to have a higher asset composition ratio, more frequently change their auditors, and are less competitive in generating sales from their total assets than non-FFR companies. In terms of moderation, board independence as a moderating variable weakens the effects of leverage on FFR while strengthening the effects of asset composition on FFR, and change in auditor weakens the relationship between capital turnover and FFR. The study highlights alarming signs for FFR prediction, providing policy implications for regulators, auditors, managers, and investors. It contributes academically by combining signaling and agency theories.